Public relations for social responsibility : affirming DEI commitment with action - Pompper, Donnalyn (Communicating responsible diversity, equity, and inclusion, 2021)
This inaugural edited collection for the Communicating Responsible Diversity, Equity, and Inclusion series presents new critical discourse alongside cutting-edge practical work at the crossroads of PR, CSR, and DEI. The collection explores the active promotion of diversity, equity, and inclusion as a public relations responsibility and provides new avenues for critiquing the ways in which power operates through public relations work and theory building. Featuring contributions from leading scholars from across the PR, CSR, and DEI fields, Public Relations for Social Responsibility explores key issues including the legal and economic frameworks thwarting authentic social responsibility and DEI, the unique social responsibility style of women and people of color managing organizations, and expanding the social responsibility critique to include non-human stakeholders and the environment. Chapters illuminate international and industrial contexts at the intersection of PR, CSR and DEI, including historical perspective on DEI roadblocks in the U.S., PR in the time of COVID-19 crises, organizational bullying, DEI, AI and PR ethics, animals as stakeholders, inclusion as CSR component, CEO activism on the African continent, and PR's responsibility in transforming society. The collection will introduce new conceptual and practical approaches highly relevant to scholars of Communication, Management and Corporate Social Responsibility in a global context.